From kiasu to kiasi : the workings of a social habitus in post-independence Singapore - Tan, Josiah Zhi Xian (Nanyang Technological University, 2022)
Today, bring up the terms “kiasu” and “kiasi” and it can be said that no Singaporeans could deny association or affiliations to this said mentality. Borrowing the sociological theories of the field and the habitus, this thesis argues that the Singaporean state during this 1980s saw the necessity for the inculcation a “kiasu” and “kiasi” habitus amongst the public, ultimately taking advantage of the said habitus to develop a docile society susceptible to the technocratic pragmatism of the ruling state. This paper will explore the major policy reforms taking place across various sectors—Education, Urban Transportation, Healthcare— during the 1980s with a post-structural lens, critically analyzing the production and dissemination of knowledge discourses by the state during this period and how this had intertwined with developing and making use of the dominant kiasu and kiasi habitus.